Five-year Plan Plantation Activity in Ramnagar Forest Division, Uttar Pradesh - Agarwala, V. P. (Indian Forester, 1957)
Rapid progress made in the extent and techniques of artificial regeneration of softwoods, sal, teak, etc., in Ramnagar Forest Division is described. Total area of 873 acres has been taken up for plantation in 1956. Much bigger single units are now being tackled than could be imagined five years before. Multi-purpose plantations integrating various objectives into single schemes are being formed. Soil working is being done by tractor, as well as by manual labour according to suitability of conditions. Special porcupine-cum-game proof fence is being ordinarily used. The 1955 Tehra (385 acres) and 1956 Phanto ( 670 acres) plantations are described. Height growth for many species in first three years in recent plantations is much superior to that described by Troup and Howard. The problem of mixtures of species is discussed. Introduction of agricultural crops, and early departmental burning of plantation areas for fire protection is referred to. The activity is of vital importance to yield valuable raw materials for industries.